Analisis Sentimen Masyarakat Terhadap Kenaikan Biaya Haji Tahun 2023 Menggunakan Metode Naïve Bayes Classifier - Hertati; Elin Haerani; Novriyanto; Fadhilah Syafria (STMIK Budi Darma, 2023)
The Indonesian government through a meeting of the Ministry of Religion and Commission IVIII of the DPR-RI agreed on the cost of organizing the Hajj pilgrimage (BPIH) i1444 iH/2023 iM, an average of IDR 90,050,637.26 per irregular pilgrimage. However, this policy gave rise to various public responses. The public's anger regarding the increase in Hajj fees in 2023 was found on the social media iTwitter. In this study, we conducted a sentiment classification analysis of Tweets to determine public opinion regarding the increase in Hajj costs in 2023 using the naïve Bayes classifier method because this method tends to be simple and easy to use. The data set used was 3000 tweets with a total of 1866 positive data, 415 negative data. This research resulted in an accuracy value of 81.46% in the 70:30 data division, in the 80:20 data division, namely 80.74% and in the data division. 90:10 which is 79.04. In this research, there were more positive responses from the public, this proves that the increase in Hajj costs in 2023 can be accepted by the public. The highest accuracy in this study was 81.46% with a 70:30 data split. It is recommended that further research use other algorithms to see a comparison of the results of different algorithms in classifying public sentiment regarding the increase in the cost of Hajj in 2023.